Bahasa Medan in Digital Interaction: A Sociolinguistic Study of TikTok Youth Culture - Hana Olivia Marpaung; Ambarita, Yessi Sherly Abigail; Alya Saqinah; Rahmadsyah Rangkuti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates how Bahasa Medan, a distinctive regional dialect from North Sumatra, is used, transformed, and sustained within the digital environment of TikTok. Drawing on Hymes’ (1972) theory of the speech community and supported by sociolinguistic frameworks from Gumperz (1982), Holmes (2013), Bell (1984), and Bucholtz and Hall (2005), the research explores how Medanese youth employ their dialect across multimodal forms of communication—spoken performances, textual captions, and interactive comment exchanges. Using qualitative descriptive methods, the study examines content from selected TikTok creators who integrate Bahasa Medan into their videos to express humor, identity, and solidarity. The findings reveal that TikTok functions as a digital speech community where dialectal expressions such as palak, sor, beserak, slek, berondok, and merajok serve as linguistic markers of belonging and cultural pride. Furthermore, users exhibit strategic code-switching among Bahasa Medan, standard Indonesian, and English to balance local authenticity with global participation. These interactions demonstrate how linguistic creativity, humor, and social engagement enable regional dialects to thrive in transnational digital spaces. The research ultimately shows that Bahasa Medan on TikTok is not merely a form of entertainment but a dynamic expression of identity, cultural continuity, and community in the era of globalized media.